Risk management framework for build, operate and transfer (BOT) projects in Kuwait - Al-Azemi, Khalid Fahad; Bhamra, Ran; Salman, Ahmed F. M. (Journal of Civil Engineering and Management, 2014)
Successful implementation of build-operate-transfer (BOT), infrastructure projects is dependent on a full and thorough analysis of factors that include social, economic and political, amongst others. Alongside the financially focused evaluations, qualitative factors will also have a strong impact on the project and so require specific techniques for the analysis. This paper presents a new evaluation framework, based on the analytical hierarchy process technique, for use in assessing the most common and significant decision factors relating to risks in BOT projects. Consultations with an expert group identified a series of risk decision factors. The results produced twenty-eight critical Risk Factors, which have a particular impact on the risks of BOT projects. The project risk framework was constructed by classifying the factors into five categories. The framework was successfully validated using a BOT project case study. This research seeks to make a valuable contribution to the field by having developed and validated a new risk evaluation framework, focused on BOT projects in Kuwait.